Persepsi Siswa Kelas XI terhadap Pemanfaatan liveworksheets.com pada Mata Pelajaran English Proficiency di SMA DEK Padang - Anne Pratiwi; Ulil Amri (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Today, the use of digital learning platforms has become an alternative learning method for students at schools, especially at DEK Padang High School. One of the learning platforms used in the English Proficiency subject at DEK Padang High School is the website at liveworksheet.com. This qualitative descriptive study aims to look at the perceptions of SMA DEK Padang students on the use of liveworksheet.com in English Proficiency subject. Data was collected through closed questionnaires and interviews were conducted as a form of verification to 30 students of class XI who had taken English Proficiency for 4 semesters. The findings of this study are 83% of DEK SMA students think that English Proficiency is interesting and fun and 81.67% of students think that using liveworksheet.com helps them master the subject matter.